MIDDLE POWER AND SYMBOLIC POWER IN CLIMATE CHANGE NEGOTIATIONS: THE CASE OF INDONESIA’S STRATEGY IN THE KATOWICE CLIMATE CHANGE CONFERENCE - Pratama, Adam; Karim, Moch Faisal (UI Scholars Hub, 2023)
This article presents a fresh perspective on international climate change negotiations by shining a light on the often-ignored concept of symbolic power within the role of middle powers, an area where current literature largely emphasizes behavioral and functional aspects. Focusing on Indonesia's participation in the 2018 United Nations Framework Convention on Climate Change Conference in Katowice, Poland, the study explores how the nation adeptly wielded symbolic power to champion the concerns of developing nations. Through strategic utilization of language and identity, Indonesia underscored three crucial negotiation points: financial support, technological transfer, and capacity building—all essential for achieving the Paris Agreement objectives. Indonesia's assertive narrative, which called for developed nations to honor their commitments to their less affluent counterparts, not only conveyed a powerful message but also enabled the country to leverage its middle power status effectively. By assuming a representative role for other developing nations, Indonesia facilitated consensus in the negotiations. This study broadens the middle power discourse, highlighting the function of symbolic power and its potential to reshape international climate policy.